Determinants of intention to become green waqf waqif in Indonesia - Rachmad, Dedy; Akbar, Nashr; Suryomurti, Wiku; Maulida, Syahdatul (Review of Islamic Social Finance and Entrepreneurship, 2025)
Purpose – This study investigated the factors influencing Muslims’ intention to participate in green waqf in Indonesia. Specifically, it examines the role of knowledge within the Theory of Planned Behavior (TPB) framework to understand how knowledge, attitudes, subjective norms, and perceived behavioral control shape the intention to become a waqif (a person who endows waqf).Methodology – This study employed a quantitative design using survey data collected from 100 Muslim respondents in Indonesia. Data were analyzed with Structural Equation Modeling (SEM) using SmartPLS 3 to test the relationships between knowledge, attitudes, subjective norms, perceived behavioral control, and intention. Findings – The findings reveal that Knowledge positively influences attitude, and both attitude and perceived behavioral control significantly impact intention to become a waqif. However, subjective norms did not significantly affect intention. Implications – This study contributes to the existing literature by extending TPB in the context of green waqf and offers insights into the role of knowledge in shaping attitudes toward green waqf. Practically, this study highlights the need for increased awareness and structured initiatives to enhance participation in green waqf, particularly through education and government-driven campaigns. Originality – This research adds to the growing literature on green waqf by applying and extending TPB with knowledge, offering fresh insights into the behavioral determinants of waqf participation, and highlighting the link between Islamic philanthropy and environmental sustainability.